A Simple Approach to Ascertain the Magnitudes of the Coefficients of 2 p-Atomic Orbitals in Each 1t-Electron Molecular Orbital of the Linear Polyenes or Polyenyl Systems - Niyaz Khan, Mohammad (1991)
A simple approach is suggesred to ascertain the magnitudes o[the coefficients o[all interacting 2p-atomic orbitals (2pAO) in each Tt-eledron moleeuw.r arbital o[the linearpolyenes ar polyenyl systems, C.H,.2' with n ranging from 2 to 28